Thermodynamic analysis and performance optimization of an Organic Rankine Cycle (ORC) waste heat recovery system for marine diesel engines. (15th March 2015) - Song, Jian; Song, Yin; Gu, Chun-wei
Abstract: Escalating fuel prices and imposition of carbon dioxide emission limits are creating renewed interest in methods to increase the thermal efficiency of marine diesel engines. One viable means to achieve such improved thermal efficiency is the conversion of engine waste heat to a more useful form of energy, either mechanical or electrical. Organic Rankine Cycle (ORC) has been demonstrated to be a promising technology to recover waste heat. This paper examines waste heat recovery of a marine diesel engine using ORC technology. Two separated ORC apparatuses for the waste heat from both the jacket cooling water and the engine exhaust gas are designed as the traditional recovery system. The maximum net power output is chosen as the evaluation criterion to select the suitable working fluid and define the optimal system parameters. To simplify the waste heat recovery, an optimized system using the jacket cooling water as the preheating medium and the engine exhaust gas for evaporation is presented. The influence of preheating temperature on the system performance is evaluated to define the optimal operating condition. Economic and off-design analysis of the optimized system is conducted. The simulation results reveal that the optimized system is technically feasible and economically attractive. Highlights: ORC is used to recover waste heat from both exhaust gas and jacket cooling water. Comparative study is conducted for different ORC systems. Thermal performance, system structure and economic feasibility are considered. Optimal preheating temperature of the system is selected.